Quality of life of Sudanese Patients with Benigan Prostatic Hyperplasia. The Oblivious Problem - Taha, Sami M; M Ahmed, Mohammed El Imam; Omran, Mustafa; Al magbool, Moneer .A.; Mustafa, Gamal; Yaseen, Diaa eldinn (Gezira Journal of Health Sciences, 2013)
Background: Although the IPSS and QOL index are universally used, they can only quantify the severity of lower urinary tract symptoms suggestive of benign prostate hyperplasia (BPH) and evaluate treatment efficacy, but cannot fully reflect the overall quality of life. Moreover, because QOL scale depends on the culture background, it is necessary to develop a Sudanese version of the scale. Objective: To evaluate the impact of BPH on the quality of life by assessing the physical, mental and stress states among patients of BPH. Methodology : This study was conducted on 424 patients with BPH in Gezira Hospital for Renal Disease and Surgery (GHRDS), Sudan. The study was cross-sectional, prospective small-scale hospital based study using simple random sampling technique. The subjects were limited to the Sudanese patients, who could hear and answer the questions of the questionnaire independently and that was done for accuracy and privacy. Taking the patient's educational level into account, all items were expressed in spoken language. The data collection tool was a questionnaire which was modified to twelve items from the BPH Quality of Life Index. Results : The majority 386 patients, 91% were physically fit. The pattern of urination was bothering to their daily life of around 320 patients/75.5%, 225 patients/53.1% of patients were worried about the outcome of the disease, 259 patients/61.1% were not concerned of having prostate cancer and 332 patients/78.2% were satisfied with their sleep. The sexual life had been affected in 201 patients/47.4%. The physical state was assessed by the ability of the patient to pray Friday Jomaa at the mosque which was 85.8% and also by attending important Sudanese obliging social activities like condolence which was (91.9%) of the patients. Conclusion : The impact of BPH on quality of life was obviously significant in the three domains; physical, mental and stress state among patients of BPH in GHRD&S.There should be a validated scale for the BPH Quality of Life Index addressing the traditional strata for Sudanese patients.